Surgical Management and Short-Term Outcome of Patients with Posterior Fossa Tumor in All Age Groups: Our Perspective (Journal of Rangpur Medical College, 2024)
Background: Different types of brain tumor can occur in the region of posterior fossa. Ependymoma, medulloblastoma and pilocytic astrocytoma occur mostly in children and rarely in adults. Brain metastases in adults are the most common malignancies at this site. Other tumors that occur in the posterior fossa are meningioma, schwannoma, hemangioblastoma, brain stem glioma and epidermoid tumors. Posterior fossa tumor has different treatment approaches and prognosis. So, an accurate diagnosis, surgical approaches, complication analysis and outcome assessment are mandatory. Objective: To evaluate the clinical aspects, surgical approach, role of preoperative shunt, post-operative complications, and short-term outcome of patients with posterior fossa tumor in different age groups. Methods: This cross-sectional observational study included 36 patients with posterior fossa tumors that were admitted and operated in the Neurosurgery Department of Rangpur Medical College Hospital between the period of November 2018 and June 2022. In each patient clinically diagnosis was confirmed by MRI of Brain with contrast followed by histopathology. Results: Out of 36 patients, 23(63.9%) patients were male and 13(36.1%) were female. Mean age was 18.01±13.95 SD years (minimum 6 months and maximum 45 years), more common in pediatric age group (36.1%